2020
DOI: 10.11604/pamj.2020.37.17.23869
|View full text |Cite
|
Sign up to set email alerts
|

Management of adnexal masses' torsion during pregnancy

Abstract: With the increased use and quality of ultrasound in pregnancy, adnexal masses are being encountered with greater frequency. Most of the time such masses are asymptomatic. It can be discovered in an emergency. Surgical intervention may cause risks to the mother and her fetus, while observation without intervention may also lead to unfavorable complications, such as ovarian torsion or the development of a tumor. Therefore, the management requires a balance between the maternal and fetal risks. We report two case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recent studies have confirmed the safety of this surgery. 13,14,18 The most representative study covering 6.5 million people in the United Kingdom 19 reflects the increasing protection of anesthetic drugs and safety of nonobstetric surgery during pregnancy. 8,20 However, there is still a lack of assessment content for long-term follow-up in earlier research.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed the safety of this surgery. 13,14,18 The most representative study covering 6.5 million people in the United Kingdom 19 reflects the increasing protection of anesthetic drugs and safety of nonobstetric surgery during pregnancy. 8,20 However, there is still a lack of assessment content for long-term follow-up in earlier research.…”
Section: Discussionmentioning
confidence: 99%
“…During the patient follow-up period, the diameter of each mass was measured. Based on the differential diagnoses of benign or malignant tumors, a 1-cm increase in a mass (as observed in the ultrasound) was considered tumor growth (6). Table 1 shows the relationship between tumor growth during pregnancy and pathological type.…”
Section: Growth Of a Persistent Adnexal Mass In Pregnancymentioning
confidence: 99%